Spatial distribution as a key factor for evaluation of soil attributes prediction at field level using online near-infrared spectroscopy - Canal Filho, Ricardo; Molin, José Paulo (Frontiers in Soil Science, 2022)
In soil science, near infrared (NIR) spectra are being largely tested to acquire data directly in the field. Machine learning (ML) models using these spectra can be calibrated adding only samples from one field; or gathering different areas to augment the data inserted and enhance models’ accuracy. Robustness assessment of prediction models usually rely on statistical metrics. However, how the spatial distribution of predicted soil attributes can be affected is still little explored, despite agriculture productive decisions depends on spatial variability of attributes. The objective of this study was to use online NIR spectra to predict soil attributes at field level, evaluating the statistical metrics and also the spatial distribution observed in prediction to compare a local prediction model with models that gathered samples from other areas. A total of 383 online NIR spectra was acquired in an experimental field to predict clay, sand, organic matter (OM), cation exchange capacity (CEC), potassium (K), calcium (Ca) and magnesium (Mg). To build ML calibrations, 72 soil spectra from experimental field (Local dataset) was gathered with 59 samples from another area nearby, in the same geological region (Geological dataset) and with this area nearby and more 60 samples from another area in a different region (Global dataset). Principal components regression was performed using k-fold (k=10) cross-validation. Clay models reported similar errors of prediction, and although Local model presented the lower R² (0.17), the spatial distribution of prediction proved that the models had similar performance. Although OM patterns were comparable between the three datasets, Local prediction, with the lower R² (0.75), was the best fitted. However, for secondary NIR response attributes, only CEC could be successfully predicted, and only using Local dataset, since the statistical metrics were compatible, but Geological and Global models misrepresented the spatial patterns in the field. Agronomic plausibility of spatial distribution proved to be a key factor for evaluation of soil attributes prediction at field level. Results suggest that local calibrations are the best recommendation for diffuse reflectance spectroscopy NIR prediction of soil attributes, and that statistical metrics alone can mispresent the accuracy of prediction.